New records and ecological data on the alien species Colasposoma dauricum and Luperomorpha xanthodera (Coleoptera: Chrysomelidae) in Italy - Giulia Magoga; Matteo Montagna (Natural History Sciences, 2023)
New records and ecological data on the alien species Colasposoma dauricum and Luperomorpha xanthodera (Coleoptera: Chrysomelidae) are provided for Italy. C. dauricum was collected during the summer of 2021 in Verbania (Piedmont), close to the border between Lombardy and Switzerland, on Rubus ulmifolius Schott, a new host plant for the species. L. xanthodera was collected both in semi-natural environments and in close proximity to gardens and greenhouses. Interestingly, among the newly reported records, the presence of L. xanthodera in the vicinity of Lago Fimon (Veneto) in 2007, only one year after its first detection in Italy, suggests that this species may have been introduced in the Country multiple times.